INTEGRATION OF DIGITAL TECHNOLOGY AND CHARACTER EDUCATION: BUILDING A RESILIENT GENERATION IN THE ERA OF THE INDUSTRIAL REVOLUTION 5.0 - Koten, Romualdus Antonius Geli; Simarmata, Hengki Mangiring Parulian (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyze the integration of digital technology in character education in the era of the Industrial Revolution 5.0 through a systematic literature review approach to 50 selected studies published in the 2020–2025 period. The results of the study show that digital literacy is the main foundation that strengthens the formation of students' character, especially in terms of honesty, responsibility, empathy, and 21st century skills. The role of teachers, families, schools, and governments has proven to be crucial in supporting implementation, while the main challenges lie in the gap in technology access, human resource readiness, and curriculum adaptation. This study also identifies research gaps, namely the limitations of integrative models that connect technology, character education, and digital resilience simultaneously, as well as the lack of empirical evidence based on the Indonesian context that is in line with the Pancasila Student Profile Strengthening Project (P5) program. Thus, this article provides a conceptual contribution in the form of new research directions and policy models that emphasize digital literacy, ethics, and critical digital citizenship as instruments for shaping the character and digital resilience of the younger generation.